Synthesis, Structure, DNA Binding, and Magnetic Properties of Dicobalt (II/III, III/III) Complexes Based on 5-(1H-benzo[d]imidazol-2-yl)-1H-imidazole-4-carboxylic Ligand. Issue 10 (2nd October 2016) - Liu, Wei; Shao, Jia; Lian, Wen-Jing; Xie, Cheng-Zhi; Xu, Jing-Yuan
ABSTRACT: Two novel dicobalt complexes, [Co II/III 2 (HImbm)(bipy)4 ](ClO4 )3 ·2H2 O (1 ) and [Co III/III 2 (HImbm)(bipy)4 ](ClO4 )4 ·CH3 OH·4H2 O (2 ) (H3 Imbm = 5-(1 H -benzo[ d ]imidazol-2-yl)-1 H -imidazole-4-carboxylic acid; bipy = 2, 2′-bipyridine), have been synthesized and characterized. Single-crystal X-ray analyses revealed that both1 and2 featured a similar HImbm-bridged dicobalt unit, except for oxidation state assignments of Co II /Co III mixed-valence in1 and Co III /Co III equal valence in2 . EB-DNA fluorescence quenching study of1 and2 suggest moderate intercalative binding modes between the compounds and DNA. Magnetic properties have been investigated for1 and the result is in agreement with the behavior of unquenched spin-orbit coupling of six-coordinated high-spin Co(II) ions.